Study On The Use Of Management Accounting Information Systems In Planning And Decision Making (PT. ASKRINDO Cabang Jambi) - Safelia, Nela; Fiqri, Sulthoni; Yuliusman, Yuliusman (Faculty of Economics and Business Universitas Jambi, 2024)
This research aims to examine the management accounting information system and to analyze the use of the management accounting information system in decision making at PT. Askrindo Jambi Branch. The research method uses a qualitative approach through data collection by interviews, observation and documentation. The research results show that PT. Askrindo Jambi Branch already has an information system called ACS (Askrindo Core System). The use of the ACS system is used in the management accounting information system for planning, and also when making decisions at PT. Askrindo's Jambi branch is interconnected between technical fields at branch level (Jambi) and then evaluated by directors at central level. Both theoretical and practical contributions are made by this study. Theoretically, it improves how MAIS successfully aligns central decision-making with branch-level operations in a service-oriented financial institution. Practically speaking, the study identifies gaps in PT Askrindo Jambi's information flow and shows how MAIS can be improved to increase responsiveness, speed up decision-making, and align operations—providing advice for comparable businesses going through digital transformation.